Optimization and mechanistic insights into silicon-doped ferrihydrite for simultaneous removal of arsenic and cadmium from contaminated water - Yuchao Mei; Zhihao Pang; Zixiang Gao; Hongyun Peng; Xianjin Tang; Yongchao Liang (Ecotoxicology and Environmental Safety, 2025)
There are often a large number of heavy metal/metalloid ions in industrial wastewater, and arsenic (As) and cadmium (Cd) mixed pollution is a common combination. Ferrihydrite (Fh) is a naturally occurring adsorbent material. It has a strong adsorption effect on As, but it is not stable, and its adsorption effect on Cd is poor. This study uses silicon doping to solve the above issues. The preparation method was optimized, and the As and Cd adsorption performance of Si-Fh was explored under different adsorption times, pH conditions, As and Cd concentrations, and coexisting ion conditions (NO3- and PO43-). It was found that, compared with freeze-drying, Si-Fh dried in an oven had higher energy efficiency while maintaining optimal weak crystallinity. Cd adsorption was increased by 4 times due to Si doping, while the As removal rate of Si-Fh could still be maintained at over 90 % compared with pure Fh. The adsorption performance reached its optimum when the Si/Fe ratio was 0.2. In addition, the simultaneous adsorption performance of Si-Fh for As and Cd is less affected by pH and coexisting ions, and is superior to that of five other common adsorbent materials. By characterizing the structure of Si-Fh before and after adsorption, we found that the surface negative charge and active hydroxyl groups of Fh significantly increased after the addition of Si. This makes it easier for Cd to approach Si-Fh and bind with hydroxyl groups. For As, although Si partially occupies the binding sites of As, the doping of Si improves the surface porosity of Fh, which facilitates the microporous adsorption of As. These findings demonstrate Si-Fh’s potential for efficient, simultaneous As/Cd remediation in wastewater treatment.